KAJIAN PENAMBAHAN NATRIUM PYROPHOSPAT UNTUK MENCEGAH BROWNING PADA PEMBUATAN TEPUNG SUKUN (Jurnal Teknologi Pangan, 2013)
Like  most  fruit - fruit,  breadfruit  prone  to  browning  after  peels.  This  is  due  to oxidation  by  air,  forming  browning,  which  will  result  in  the  final  result  breadfruit  flour  for making good quality flour is white, and dry.   Pyrophospat  Sodium  is  an  ingredient  that  can  serve  as  a  barrier  to  browning reactions,  primarily  as  a  metal  fastener  and  thus  antioxidants  Pyrophospat  Sodium  is  very effective to prevent discoloration of foods during preparation or storage.   The  best  results  obtained  from  this  research  is  the  weight  of  9  grams  Sodium Pyrophospat soaking 21 minutes in which the resulting yield of 21.69%.  While the best water content of  8.09%  with  the use  of  one  gram  of sodium  Pyrophospat  with immersion  time  for  9 minutes.Keywords: Breadfruit, Sodium Pyrophospat, Breadfruit Flour.